Permeable reactive barriers for groundwater contaminant removal: Mechanisms, materials, and challenges - Meky, Mohammed Mansour; Hassan, Nagy Ali; Soussa, Hoda; Gabr, Mohamed Elsayed (Brawijaya University, 2025)
Groundwater pollution from industrial, agricultural, and municipal sources presents a critical environmental challenge, necessitating adopting sustainable remediation strategies. As a result of this crucial issue, groundwater remediation strategies have gained traction, with a particular focus on sustainable techniques. Among these, Permeable Reactive Barriers (PRBs) are considered a promising, low-cost, and sustainable groundwater remediation approach. This review examines the main concept, configurations, design procedures, and applications of PRBs, emphasizing their role in intercepting and degrading pollutants through various removal mechanisms such as adsorption, ion exchange, and microbial activity based on the used reactive materials. The selection of reactive materials is explored concerning their effectiveness in contaminant removal, while different PRB configurations are analyzed for their environmental benefits, hydraulic performance, and cost efficiency. This study also analyzes the challenges associated with PRBs, including site heterogeneity, material selection, and maintenance requirements. By synthesizing existing research and real-world applications, this study provides a detailed evaluation of PRBs as a promising technology for sustainable groundwater remediation.